Modern trends in educational migration in Russian Federation (Journal of Philosophy Culture and Political Science, 2019)
The article discusses the main trends and features of the development of educational (training) migration in Russia in the era of globalization and the internationalization of the educational space. Modern consideration of the problems of educational migration is relevant, thus social, economic and political changes in the post-Soviet space affected attitudes, motivation and readiness for educational migration from various groups of society, and above all, the younger generation. The author considers the factors influencing the scale, structural characteristics and directions of the flows of external and internal educational migration in Russia. The effects of educational migration and the possibilities of managing it in order to prevent «brain drain» are analyzed. Regulation of this area is very difficult, and an important state objectives, determining the development potential of any state, capable of ensuring the quality and quantity of human capital. This article was prepared within the framework of the MES RK project «Educational migration from Kazakhstan: trends, factors and socio-political consequences»; Oneof the priority objectives of this project is to study the experience of foreign countries, in particular theRussian Federation, in the field of monitoring and regulating student migration, identifying mechanisms to stimulate the return of young people after receiving education abroad.Key words: international educational migration, higher education, Russia, internationalization ofeducation, academic mobility.